2001
DOI: 10.1055/s-0037-1615644
|View full text |Cite
|
Sign up to set email alerts
|

Platelet Glycoprotein Receptor IIIa Polymorphism PlA1/PlA2 and Coronary Risk: a Meta-Analysis

Abstract: SummaryMembrane glycoprotein IIb/IIIa plays a major role in platelet function. The gene encoding the glycoprotein IIIa shows a common polymorphism PlA1/PlA2 that was variably associated with vascular disease. To clarify the role of PlA1/PlA2 polymorphism in coronary risk, a meta-analysis of published data was conducted. Studies were identified both by MEDLINE searches, and hand searching of journals and abstract books.A total of 34 studies for coronary artery disease (CAD), and 6 for rest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
77
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 109 publications
(82 citation statements)
references
References 39 publications
5
77
0
Order By: Relevance
“…They also observed that the overall OR for adverse outcome after revascularization procedures was 1.31 (95% CI, 1.10-1.56). 66 In agreement with these results, Galasso et al 67 demonstrated that the PLA2 allele is associated with thrombotic cardiovascular complications in 400 consecutive patients with CAD undergoing percutaneous coronary intervention. Moreover, the combination of the PLA2 allele of GPIIIa and the 807T allele of GPIa was found to confer additional risk for the development of carotid atherosclerosis and arterial thrombosis in patients with type 2 diabetes.…”
mentioning
confidence: 67%
See 1 more Smart Citation
“…They also observed that the overall OR for adverse outcome after revascularization procedures was 1.31 (95% CI, 1.10-1.56). 66 In agreement with these results, Galasso et al 67 demonstrated that the PLA2 allele is associated with thrombotic cardiovascular complications in 400 consecutive patients with CAD undergoing percutaneous coronary intervention. Moreover, the combination of the PLA2 allele of GPIIIa and the 807T allele of GPIa was found to confer additional risk for the development of carotid atherosclerosis and arterial thrombosis in patients with type 2 diabetes.…”
mentioning
confidence: 67%
“…65 Accordingly, in a meta-analysis including 34 studies on CAD patients published until June 2000 and 6 studies on patients with restenosis after revascularization (9095 cases and 12,508 controls), Di Castelnuovo et al 66 found an overall OR of 1.10 (95% CI, 1.03-1.18) and 1.21 (95% CI, 1.05-1.38) in CAD patients carriers of the PLA2 allele and in subjects younger than 60 years, respectively. They also observed that the overall OR for adverse outcome after revascularization procedures was 1.31 (95% CI, 1.10-1.56).…”
mentioning
confidence: 99%
“…If not otherwise reported in the study, it was assumed that wine contains 12% and beer 6% ethanol. Other sources of heterogeneity in the methodological quality of the studies were taken into account by performing sensitivity analysis, 47,48 and prespecified subgroups were considered according to type of cohort or event in case group, sex, adjustment for different types of alcoholic beverages or for indicators MI indicates myocardial infarction; N, number of patients, size of the cohort, or number of cases/number of controls; adjustment A, studies had not taken into account different types of alcoholic beverage; and adjustment B, bias of combined drinking was either excluded or taken into account.…”
Section: Data Extractionmentioning
confidence: 99%
“…Since the study of Weiss et al is the first study which has reported P1A2 polymorphism as a risk factor for MI, some studies in the literature have been shown inconsistent results. 9,13,21,22 Several studies demonstrated that the P1A2 polymorphism is a strongly associated with MI. [23][24][25] Rest of studies did not find any results to verify this relationship.…”
Section: Discussionmentioning
confidence: 99%